2019
DOI: 10.31080/asps.2019.03.0340
|View full text |Cite
|
Sign up to set email alerts
|

Why There is an Increased Number of Deaths from Heroin Mixed with Fentanyl in the USA: Potential Roles of Unrecognized Hypomagnesemia and Elevated Levels of Ceramides and Platelet-Activating Factor Particularly in Brain Stem Area and Potential Relationship to Euphoria and Hallucinations

Abstract: Currently, there is a widespread number of deaths, particularly in the USA, from ingestion/imbibing a combination of heroin and fentanyl. Young and old adults are becoming rapidly addicted to this drug combination. Many of these victims believe they are being sold heroin unaware that the latter is often "laced" with fentanyl. Until now, the mechanism(s) for inducing coma followed by death has been thought to be respiratory and cardiac failure. However, new evidence from human and experimental animal studies, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…5,17,22,25,26,100,114 These genotoxic effects were found to result in release of cytokines and chemokines from primary cultured vascular smooth muscle and human endothelial cells by our group. 17,75,77,78,100,101,106 molecules required for transformation, growth and differentiation of macrophages/monocytes, vascular muscle and endothelial cells in the evolving atherogenic process. [11][12][13]109 Supplemental, elevated dietary levels of Mg ameliorate/inhibit the latter transformations, at least in experimental animals.…”
Section: Nf-kb and Proto-oncogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,17,22,25,26,100,114 These genotoxic effects were found to result in release of cytokines and chemokines from primary cultured vascular smooth muscle and human endothelial cells by our group. 17,75,77,78,100,101,106 molecules required for transformation, growth and differentiation of macrophages/monocytes, vascular muscle and endothelial cells in the evolving atherogenic process. [11][12][13]109 Supplemental, elevated dietary levels of Mg ameliorate/inhibit the latter transformations, at least in experimental animals.…”
Section: Nf-kb and Proto-oncogenesmentioning
confidence: 99%
“…[11][12][13]109 Supplemental, elevated dietary levels of Mg ameliorate/inhibit the latter transformations, at least in experimental animals. 25,26,100,101,106…”
Section: Nf-kb and Proto-oncogenesmentioning
confidence: 99%
“…with Prinzmetal-variant angina [8], 105 stroke patients [25], and over 150 patients with diverse substances of abuse brought into our ERs [2][3][4], unpublished findings, and using specificallydesigned electrodes for measurement of serum ionized Mg levels [7][8][9][10][11] revealed that, on average, there was a 35-45% decrease in the ionized Mg. Measurement of interleukin 1a, TNF-alpha, and c-reactive protein indicated a strong correlation (r=<0.001) to the serum ionized Mg level [37,38] unpublished findings.…”
Section: Examination Of the Sera Of Approximately 35 Cardiac Patientsmentioning
confidence: 99%
“…to exhibit elevated levels of alcohol, various psychedelic drugs, cocaine, amphetamines, heroin-fentanyl and/or marijuana [2][3][4] unpublished studies. Several recent studies, including our own, demonstrate that many heart attack victims, subjects with myocardial infarctions, congestive heart failure and/or strokes exhibit similar reduced serum levels of Mg2+ when looked for [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%